2021
DOI: 10.2174/1573407216666201228114004
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Phytochemical and Pharmacological Profile of Morus alba Linn

Abstract: Background: Morus alba Linn. commonly known as white mulberry, belongs to the family Moraceae, is a promising traditional medicine. In Asia, besides its use in the preparation of delicacies, every part of this plant is utilized in traditional medicine. Over the past decade, studies related to identification and isolation of biologically active compounds, with flavonoids as the major class of phytoconstituents, from this plant has been reported. These phytoconstituents are not only found to be beneficial for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 169 publications
0
1
0
Order By: Relevance
“…The traditional uses of these trees included all parts, but nutrition was and still the most important. In this review, we focused on antidiabetics and related activities, yet numerous publications reported many other traditional uses [176][177][178]. And as presented in section 1, the leading species in traditional antidiabetic activity are M. alba and M. nigra, so this is the general outcome in all aspects of traditional uses and modern medicinal research fi ndings for this genus.…”
Section: Discussionmentioning
confidence: 99%
“…The traditional uses of these trees included all parts, but nutrition was and still the most important. In this review, we focused on antidiabetics and related activities, yet numerous publications reported many other traditional uses [176][177][178]. And as presented in section 1, the leading species in traditional antidiabetic activity are M. alba and M. nigra, so this is the general outcome in all aspects of traditional uses and modern medicinal research fi ndings for this genus.…”
Section: Discussionmentioning
confidence: 99%